2006
DOI: 10.1007/s11103-005-5817-8
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interaction between the Tobacco Mosaic Virus Helicase Domain and the ATP-bound Resistance Protein, N Factor during the Hypersensitive Response in Tobacco Plants

Abstract: Plants cope with pathogens with distinct mechanisms. One example is a gene-for-gene system, in which plants recognize the pathogen molecule by specified protein(s), this being called the R factor. However, mechanisms of interaction between proteins from the host and the pathogen are not completely understood. Here, we analyzed the mode of interaction between the N factor, a tobacco R factor, and the helicase domain (p50) of tobacco mosaic virus (TMV). To this end, domain dissected proteins were prepared and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 52 publications
3
119
0
Order By: Relevance
“…Direct R-Avr interaction has been detected for seven R proteins: Pi-ta (Jia et al, 2000), RRS1-R (Deslandes et al, 2003), N (Ueda et al, 2006), L5/L6 (Dodds et al, 2006), M (Catanzariti et al, 2010), RPP1 (Krasileva et al, 2010;Chou et al, 2011), and Pik/km/kp/ks/kh (Kanzaki et al, 2012). For some of them, it also has been demonstrated that physical interaction is required for resistance, validating the direct recognition model.…”
Section: Introductionsupporting
confidence: 59%
“…Direct R-Avr interaction has been detected for seven R proteins: Pi-ta (Jia et al, 2000), RRS1-R (Deslandes et al, 2003), N (Ueda et al, 2006), L5/L6 (Dodds et al, 2006), M (Catanzariti et al, 2010), RPP1 (Krasileva et al, 2010;Chou et al, 2011), and Pik/km/kp/ks/kh (Kanzaki et al, 2012). For some of them, it also has been demonstrated that physical interaction is required for resistance, validating the direct recognition model.…”
Section: Introductionsupporting
confidence: 59%
“…This ligand-receptor model was supported by the fact that some Avr gene products are small and colocalize with R gene products, most of which encode receptor-like proteins carrying Leu-rich repeats (LRRs). Indeed, direct binding of a few R-Avr combinations was found, consistent with a receptor-ligand mode of action (e.g., Jia et al, 2000;Deslandes et al, 2003;Dodds et al, 2006;Ueda et al, 2006). However, for a number of R-Avr combinations, physical interactions have not been observed, and perception is thought to be indirect.…”
mentioning
confidence: 76%
“…Work on animal NBS-containing proteins and recent work on the I-2 and N proteins of tomato and tobacco has indicated that ATP binding state may play a key role in NBS-LRR protein activation (13,14,22,23). In the I-2 protein, amino acid substitutions that reduce ATP hydrolysis, but not ATP binding, cause constitutive activation of I-2, whereas substitutions that inhibit ATP binding eliminate signaling (14).…”
Section: Pbs1mentioning
confidence: 99%